2018
DOI: 10.1107/s2053229618013037
|View full text |Cite
|
Sign up to set email alerts
|

A new hexamolybdate-based copper–2,2′-biimidazole coordination polymer serving as an acid catalyst and support for enzyme immobilization

Abstract: The hydrothermal reaction of (NH4)3[CoMo6O24H6]·7H2O (CoMo6), CuCl2·2H2O and 2,2′‐biimidazole (H2biim) led to the formation of a new coordination polymer, namely poly[diaquabis(2,2′‐biimidazole)hexa‐μ3‐oxo‐octa‐μ2‐oxo‐hexaoxodicopper(II)hexamolybdate(VI)], [Cu2Mo6O20(C6H6N4)2(H2O)2]n (Cu‐Mo6O20), at pH 2–3. It is obvious that in the formation of crystalline Cu‐Mo6O20, the original Anderson‐type skeleton of heteropolymolybdate CoMo6 was broken and the new isopolyhexamolybdate Mo6O20 unit was assembled. In Cu‐Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Within the overall literature of CP-POMs, assemblies with polyoxomolybdates constitute an important sub-class. Some of the important polyoxomolybdates reported within such compounds include both the iso-polyoxometalate types, such as the tetramolybdate {Mo 4 O 13 }, 23,24 the hexamolybdate {Mo 6 O 24 }, [25][26][27] the octamo-lybdate {Mo 8 O 26 }, [28][29][30][31] and the decamolybdate {Mo 10 O 33 } assemblies, [32][33][34] and the hetero-polyoxometalate types, especially those based on the {XMo 12 O 40 }-type (X = Si IV , P V ) Keggin unit derivatives, [35][36][37][38][39] and the {(AO 3 X) 2 Mo 5 O 15 }-type pentamolybdate unit derivatives (X = O, C; A = P V , S VI , As V , Se VI , Te VI ). 40 The pentametalate ion is a unique hetero-polyoxometalate structure, wherein a circular and nearly planar five metal polyhedral unit assembly, {M 5 O 15 } (M = Mo, W), is coordinated on either side by tetrahedral hetero-groups from main-group elements.…”
Section: Introductionmentioning
confidence: 99%
“…Within the overall literature of CP-POMs, assemblies with polyoxomolybdates constitute an important sub-class. Some of the important polyoxomolybdates reported within such compounds include both the iso-polyoxometalate types, such as the tetramolybdate {Mo 4 O 13 }, 23,24 the hexamolybdate {Mo 6 O 24 }, [25][26][27] the octamo-lybdate {Mo 8 O 26 }, [28][29][30][31] and the decamolybdate {Mo 10 O 33 } assemblies, [32][33][34] and the hetero-polyoxometalate types, especially those based on the {XMo 12 O 40 }-type (X = Si IV , P V ) Keggin unit derivatives, [35][36][37][38][39] and the {(AO 3 X) 2 Mo 5 O 15 }-type pentamolybdate unit derivatives (X = O, C; A = P V , S VI , As V , Se VI , Te VI ). 40 The pentametalate ion is a unique hetero-polyoxometalate structure, wherein a circular and nearly planar five metal polyhedral unit assembly, {M 5 O 15 } (M = Mo, W), is coordinated on either side by tetrahedral hetero-groups from main-group elements.…”
Section: Introductionmentioning
confidence: 99%
“…evaluated in 2012 the WOC activity of two Co-containing Anderson-and Evans-Showell-type anions, i.e., [CoMo 6 O 24 H 6 ] 3-(Co-POM-Mo) and [Co 2 Mo 10 O 38 H 4 ] 6-(Co 2 -POM-Mo), respectively(Tanaka et al, 2012). Both anions are used extensively as starting materials to produce a variety of salts and functionalized metal complexes(An et al, 2017;Sang et al, 2018). In the [CoMo 6 O 24 H 6 ] 3anion, six assembled {MoO 6 } octahedral units are arranged around a central CoO 6 system to form the Andersontype polyoxometalate in Figure4B, while the [Co 2 Mo 10 O 38 H 4 ] 6anion can be seen as a dimer of two monolacunary Anderson [CoMo 5 H 2 O 19 ] 3clusters, assembled via two hexacoordinate CoO 6 units with shared edges, producing an acute angle of nearly 45 °between them (Figure4C)(An et al, 2017).Catalytic studies showed that these small Mo-based POMs have capabilities for O 2 generation at basic pH under the typical visible light-driven system based in the [Ru(bpy)2] 2+ /Na 2 S 2 O 8 pair.…”
mentioning
confidence: 99%